Utilizing Vasopressors: Critical Care Advances in the Emergency Department - Rubero, José A. (Revista Cubana de Medicina Intensiva y Emergencias, 2017)
In Summary….. • We reviewed the types of shock and their pathophysiology • We identified the mechanisms that the different vasopressors can help us in treating shock • Now, we can choose what will be the better vasopressor depending the type of shock